Peran Keluarga dalam Pembentukan Akhlak Islami pada Anak-Anak: Perspektif Akidah Akhlaq - Najamudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The formation of Islamic morals in children requires a significant role from the family as the smallest unit in society. In this context, the perspective of akhlaq becomes the main foundation that guides families in guiding children towards behavior that is in accordance with Islamic teachings. This research uses a qualitative approach and case study design to explore the role of the family in the formation of Islamic morals in children, taking into account the perspective of akhlaq. Data were collected through in-depth interviews with family members and direct observation of family interactions. The results show that the family has a central role in the formation of children's Islamic morals, with the values of akhlaq being the main guideline in this process. This research provides a deeper understanding of the importance of family and the perspective of the creed of akhlaq in the formation of Islamic morals in children.